Influence of guided inquiry on science literacy in biodiversity with islamic values - Adela, Chaira Dela; Zulfiani, Zulfiani; Solihin, Solihin (STKIP Persada Khatulistiwa Sintang, 2025)
The literacy level of science students in Indonesia is classified as low, especially in integrated with biology and Islamic values. This is influenced by ongoing learning, teacher-centered, limited implementation, learning is active, and a lack of integration of Islamic values in learning science in the Madrasah. Therefore, this research was conducted to now the influence of learning models inquiry guided by the ability of literacy science student class X on the material diversity and biologically integrated Islamic values at MAN 21 Jakarta. Research: This used quasi- quasi-experimental design with a pretest-posttest control group design. Inquiry model guided is an involved learning model students in a way active scientific investigation with teacher guidance through worksheets Students (LKPD), teaching modules, and resources relevant to learning, as well as blending Islamic values to increase student understanding in a way. Instrument study in the form of a PISA-based open-constructed response test. The results of the analysis show there is a significant difference between class experiments and class controls after application of the inquiry-guided learning model. This shows that learning model inquiry-guided is effective in increasing literacy in science students.